Protocolo de orientação para o autocuidado de pacientes submetidos à cirurgia bariátrica: atuação do enfermeiro - Felix, Lidiany Galdino (2009)
Bariatric Surgery is currently being considered more effective treatment of morbid obesity. In the face of increased the number of surgeries performed in the country and the complexity of patient care, this study obeso was a main building guidance Protocol for the client self-care in the pre and post surgery Bariatric Surgery, substantiated in the General Theory of Orem self-care. The methodological kind of research was used and it is made up of four phases: first stage: identification of empirical indicators for therapy of self-care demand carried out through a systematic review of the literature on nursing care to the patient undergoes Bariatric Surgery, which resulted in the structuring of the data collection form, adapted the theory of self-care of Orem; second stage: determination of deficits of self-care (DAC) achieved through an exploratory study and descriptive qualitative approach, with the following-31 customers, being 26 Bariatric Surgery candidates and 06 patients wait were included in bariatric surgery group of a teaching hospital, in the city of João Pessoa PB, during the period from April to June 2009. Data collection has led to the identification of gaps of self-care and consequently to nursing diagnoses based on taxonomy Nanda-I; third stage: Nursing systems development for DAC identified-the nursing care planning, with the determination of the goals, objectives, aid method, type of system and nursing interventions; fourth stage:structuring of nursing care protocol and guidance for self-care patient pre and post surgery Bariatric Surgery constructed from self-care demands identified. Demonstrated the importance of education and the patient staging self-care represent for the recovery of the patient and the achievement of the success of surgery. It is hoped that this study will contribute to improving the quality of nursing care to the patient bariátrico and serves as a parameter to that other health institutions to develop their own assistive protocols.